Hierarchical supply chain planning architecture for integrated analysis of stability and performance. (1st October 2007) - Son, Young-Jun; Venkateswaran, Jayendran
In this paper, a novel architecture that allows a multi-scale federation of interwoven simulations and decision models to support integrated analysis of stability and performance in hierarchical production planning for supply chain networks is proposed. The proposed scheme is divided into four stages: plan stability analysis, plan optimisation, schedule optimisation and concurrent decision evaluation. The plans are more robust against future disturbances and more feasible for implementation than those from the conventional methods. Detailed functional and process models of the proposed system are specified using formal IDEF tools. The proposed approach is demonstrated using a realistic three-echelon supply chain system.